Sustainable Client-Driven Marketing Strategies of Quantity Surveying Firms in the Built Environment - Ebunoluwa, Esther Ilori; Ojo, Grace Kehinde (International Journal of Sustainable Construction Engineering and Technology, 2023)
Marketing strategy had been understood to mean the way and manner in which a firm create and achieve a profitable customer relationship in a competitive environment. However, not all strategies could capture the attention of clients in such a competitive business environment. Therefore, this study seeks to identify marketing strategies that drive clients in engaging the services of quantity surveying firms for the sustainability of the firms in the built environment. The opinions of 46 registered quantity surveying firms in Lagos, Oyo and Ondo States on the usage and effectiveness of sustainable customer-driven marketing strategies were obtained through a well-structured questionnaire. The surveyed respondents’ quantity surveying firms were randomly sampled in the selected locations. Mean Response Analysis (MRA) and Analysis of Variance (ANOVA) were used to analyze the data collected. Findings show that professional-client relationship (MS=4.13) is the most frequently used (MS=4.17) and effective (MS=4.13) marketing strategy that drives clients and sustains the quantity surveying firms. This is closely followed by follow-up and expanding service to existing clients. Furthermore, the view of the respondents on the effectiveness of professional-client relationship (p-value=0.104) and follow-up (p-value=0.157) marketing strategies were the same at P>0.05.  However, a significant difference existed in the view of respondents on one marketing strategy i.e. expanding service to existing clients (p-value=0.019). The study concluded that professional-client relationship and follow-up are the strategies that drive the attention of the clients mostly in the study area; this increases the chances of firms’ sustainability in the built environment. The implication of this is that quantity surveying firms will much more survive in the competitive environment using these highly effective sustainable client-driven marketing strategies.